Between Tradition and Transformation: Islamic Ethical Perspectives on Minimarket Impact in Rural Indonesia - Shohiburrahman Shohiburrahman; Maksum Maksum; Ciptia Khoirulina Sanawati (Faculty of Sharia and Islamic Economic, Universtas Annuqayah, 2025)
This study examines the impact of modern retail establishments (minimarkets) on traditional grocery stores in Ganding District, Indonesia, through both conventional retail competition frameworks and Islamic ethical principles. Employing a qualitative case study methodology with data from four traditional grocery store owners, the research investigated perceptions, business impacts, and adaptation strategies. Findings reveal predominantly negative perceptions among grocery store owners, with significant revenue declines averaging 31.25%. Analysis identified differential impacts across product categories and limited adaptation efforts constrained by capital limitations and insufficient market capabilities. When evaluated through Islamic ethical principles of 'adl (justice), maslahah (public interest), ihsan (excellence), and ta'awun (cooperation), these competitive dynamics raise important considerations regarding market balance and community welfare. The research contributes to retail transformation theory while suggesting policy implications including enhanced zoning regulations and cooperative business models, highlighting the need for balanced approaches that respect traditional economic structures while accommodating modernization benefits.